Characteristics of Dye-Sensitized Solar Cell Assembled from Modified Chitosan-Based Gel Polymer Electrolytes Incorporated with Potassium Iodide - Aimi Mahirah Zulkifli; Nur Izzah Aqilah Mat Said; Shujahadeen Bakr Aziz; Elham Mohammed Ali Dannoun; Shameer Hisham; Shahan Shah; Amnani Abu Bakar; Zul Hazrin Zainal; Hairul Anuar Tajuddin; Jihad Mohammed Hadi; Mohamad Ali Brza; Salah Raza Saeed; et al. (Molecules, 2020)
In the present work, phthaloyl chitosan (PhCh)-based gel polymer electrolytes (GPEs) were prepared using dimethylformamide (DMF) as a solvent, ethyl carbonate (EC) as a co-solvent, and a set of five quaternaries of potassium iodide (KI) as a doping salt, which is a mixed composition of iodine (I2). The prepared GPEs were applied to dye-sensitized solar cells (DSSC) to observe the effectiveness of the electrolyte, using mesoporous TiO2, which was sensitized with N3 dye as the sensitizer. The incorporation of the potassium iodide-based redox couple in a polymer electrolyte is fabricated for dye-sensitized solar cells (DSSCs). The number of compositions was based on the chemical equation, which is 1:1 for KI:I2. The electrical performance of prepared GPE systems have been assessed using electrical impedance spectroscopy (EIS), and dielectric permittivity. The improvement in the ionic conductivity of PhCh-based GPE was observed with the rise of salt concentration, and the maximum ionic conductivity (4.94 × 10−2 S cm−1) was achieved for the 0.0012 mol of KI:I2. The study of dielectric permittivity displays that ions with a high dielectric constant are associated with a high concentration of added ions. Furthermore, the gel polymer electrolyte samples were applied to DSSCs to detect the conversion effectiveness of the electrolytes. For electrolytes containing various content of KI:I2 the highest conversion efficiency (η%) of DSSC obtained was 3.57% with a short circuit current density (Jsc) of 20.33 mA cm−2, open-circuit voltage (Voc) of 0.37 V, fill factor (FF) of 0.47, as well as a conductivity of 2.08 × 10−2 S cm−1.